Probing biotin receptors in cancer cells with rationally designed fluorogenic squaraine dimers. Issue 31 (29th July 2020) - Fam, Kyong T.; Collot, Mayeul; Klymchenko, Andrey S.
Abstract : Rational design of self-quenched squaraine dimers bearing biotin yielded a bright fluorogenic probe that can distinguish cancerous from non-cancerous cells. Abstract : Fluorogenic probes enable imaging biomolecular targets with high sensitivity and maximal signal-to-background ratio under non-wash conditions. Here, we focus on the molecular design of biotinylated dimeric squaraines that undergo aggregation-caused quenching in aqueous media through intramolecular H-type dimerization, but turn on their fluorescence in apolar environment due to target-mediated disaggregation. Our structure–property study revealed that depending on the linkers used to connect the squaraine dyes, different aggregation patterns could be obtained (intramolecular dimerization versus intermolecular aggregation) leading to different probing efficiencies. Using a relatively short l -lysine linker we developed a bright fluorogenic probe, Sq2 B, displaying only intramolecular dimerization-caused quenching properties in aqueous media. The latter was successfully applied for imaging biotin receptors, in particular sodium-dependent multivitamin transporter (SMVT), which are overexpressed at the surface of cancer cells. Competitive displacement with SMVT-targets, such as biotin, lipoic acid or sodium pantothenate, showed Sq2 B targeting ability to SMVT. This fluorogenic probe for biotin receptors could distinguish cancer cells (HeLa and KB) from model non-cancer cell lines (NIH/3T3 and HEK293T). The obtained results provide guidelines for development of new dimerization-based fluorogenic probes and propose bright tools for imaging biotin receptors, which is particularly important for specific detection of cancer cells.